IMPROVEMENT OF LAND RELATIONS IN AGRICULTURE OF UZBEKISTAN AND INNOVATIVE APPROACHES - Begamova Nasiba Kholmurzaevna (Modern American Journals, 2025)
The article highlights large-scale reforms carried out in Uzbekistan’s agricultural sector, ensuring food security, and the rational use of land and water resources. It analyzes measures for the gradual introduction of market relations in agriculture, the development of household and dehkan farms, the widespread application of water-saving technologies, and the enhancement of export potential. In addition, the role of state policy in supporting agricultural producers, improving land relations, and increasing the population’s income is emphasized. The author presents priority directions for the sustainable development of the agricultural sector under climate change, as well as mechanisms for the effective use of existing opportunities.
Keywords: Agriculture, food security, water resources, household farming, reforms, agrarian policy, export